Effect of sulphur on soil pH, growth and productivity of rape seed plant - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
A field trial was conducted in Experimental Station of The Field Crops Department – College Of Agriculture In Abu Ghraib, University of Baghdad to assess the effect of sulphur applications and the time after application on pH and EC of soil sample solutions ,and on the growth and yield of rape seed (Brassica napus L.)A split plot design was used with four replications , The main plot included four sulphur applications levels (0,2000,3000,4000Kg S/ha) the sub plot were the time after application (0,1,2,and 3 moths) .Sulphur application significantly decreased soil pH value ,although that decrease reached minimum parameter after two months from application date .Rather increment of sulphur application level significantly raised soil EC value, So that value decreased continuously with time after the application .Sulphur application level affected significantly increased plant height/cm and decreased seed oil content percent but not affected in seed yield /plant.